IMPLEMENTASI MODERASI BERAGAMA PADA MASYARAKAT DESA BALONGGARUT KECAMATAN KREMBUNG KABUPATEN SIDOARJO - Dewi Himmatul Agustin; I Wayan Arsana (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2023)
This research is based on social life regarding the implementation of religion in the community of Balonggarut Village, Krembung Subdistrict, Sidoarjo Regency. Diversity is an ancestral heritage. The aims of this study is to: 1) To examine the implementation of religious moderation in the community of Balonggarut Village, Krembung District, Sidoarjo Regency. 2) To determine the role of religious leaders in realizing religious moderation in Balonggarut Village, Krembung Subdistrict, Sidoarjo Regency. 3) To determine the role of community leaders in realizing religious moderation in Balonggarut Village, Krembung Subdistrict, Sidoarjo Regency. This research uses empirical juridical methods that are qualitative descriptive with interview, observation, and documentation data collection techniques. This study showed the result that community understood religious moderation so that they respect. In religious moderation, the role of religious leaders is always to get closer to communicate and preach to guide goodness to the people. the role of community leaders always gives understanding to the younger generation to always respect and appreciate the differences that exist. Keywords: Religious Moderation, Tolerance, Religiuos Leaders, Community Leaders.